Effect of simulation training on nurse leadership in a shared leadership model for cardiopulmonary resuscitation in the emergency department. (27th August 2020) - Armstrong, Patrick; Peckler, Brad; Pilkinton‐Ching, Jodie; McQuade, David; Rogan, Alice
Abstract: Objective: Empowering a senior nurse in a shared leadership role has been proposed as a more efficient set up for the cardiac arrest team in ED. In this model, a senior nurse leads the cardiac arrest algorithm which allows cognitive off‐loading of the lead emergency physician. The emergency physician is then more available to perform tasks such as echocardiography and exclude reversible causes. Simulation provides an opportunity for training and practice of this shared leadership model. We hypothesised that a structured simulation training programme that focused on implementing a nurse and doctor shared leadership model for cardiopulmonary resuscitation (CPR), would improve leadership and teamwork quality in the setting of cardiac arrest as measured by a Trauma Non‐technical Skills (T‐NOTECHS) teamwork scale. Methods: Fifteen senior ED nurses participated in this pre‐interventional post‐observational study. Training consisted of a didactic course on team leadership and crisis resource management (CRM) followed by 4 × 10‐min resuscitation scenarios with a structured debrief focusing on team leadership skills and CRM. The primary outcome was measured on scenarios 1 and 4 using a modified T‐NOTECHS teamwork scale. Results: A statistically significant increase in the T‐NOTECHS scale was detected for the measures of leadership ( P = 0.0028), CRM ( P = 0.0001), adherence to New Zealand Resuscitation Council ALS algorithm ( P = 0.0088) and situational awareness ( P = 0.0002). Conclusion: The present study shows that a short simulation training programme improved nurse leadership and teamwork performance in the setting of a shared leadership model for CPR in the ED which could easily be replicated in other departments. Abstract : Empowering a senior nurse in a shared leadership role has been proposed as a more efficient setup for the cardiac arrest team in ED. We hypothesised that a structured simulation training programme that focused on implementing a nurse and doctor shared leadership model for CPR, would improve leadership and teamwork quality in the setting of cardiac arrest as measured by a Trauma Non‐technical Skills (T‐NOTECHS) teamwork scale. The present study showed that a short simulation training programme improved nurse leadership and teamwork performance in the setting of a shared leadership model for CPR in the ED which could easily be replicated in other departments.